2006
DOI: 10.1523/jneurosci.0099-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Time of Prenatal Immune Challenge Determines the Specificity of Inflammation-Mediated Brain and Behavioral Pathology

Abstract: Disturbance to early brain development is implicated in several neuropsychiatric disorders including autism, schizophrenia, and mental retardation. Epidemiological studies have indicated that the risk of developing these disorders is enhanced by prenatal maternal infection, presumably as a result of neurodevelopmental defects triggered by cytokine-related inflammatory events. Here, we demonstrate that the effects of maternal immune challenge between middle and late gestation periods in mice are dissociable in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

59
695
8
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 713 publications
(764 citation statements)
references
References 57 publications
59
695
8
2
Order By: Relevance
“…Here, we focused on adult spatial exploration, sensorimotor gating and selective associative learning, because previous reports in rodents have repeatedly demonstrated that prenatal PolyI:C exposure leads to functional abnormalities in these neuropsychological domains when the animals reach adult age. [14][15][16][17][18][19] First, spatial exploration was studied in an open field by focusing on the time the animals spent in the central area of the field during a 30-min test period. This test is widely applied to assess explorative behavior in rodents.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Here, we focused on adult spatial exploration, sensorimotor gating and selective associative learning, because previous reports in rodents have repeatedly demonstrated that prenatal PolyI:C exposure leads to functional abnormalities in these neuropsychological domains when the animals reach adult age. [14][15][16][17][18][19] First, spatial exploration was studied in an open field by focusing on the time the animals spent in the central area of the field during a 30-min test period. This test is widely applied to assess explorative behavior in rodents.…”
Section: Resultsmentioning
confidence: 99%
“…Fetal brains were extracted under visual guidance using a dissecting microscope (Stemi 2000-C; Zeiss, Oberkochen, Germany), as described previously. 16,17 Each fetal brain sample was weighed, placed in 1-ml Eppendorf (Hamburg, Germany) tubes, and stored at À801C until further processing (see below). To assess the long-term cytokine effects of prenatal PolyI:C exposure, pregnant macIL-10tg and wt dams were administered with PolyI:C or vehicle on GD 9 as described above, and the animals were allowed to give birth.…”
Section: Collection Of Fetal and Adult Brain Tissue Samplesmentioning
confidence: 99%
See 3 more Smart Citations